2011
DOI: 10.1007/s11434-011-4444-9
|View full text |Cite
|
Sign up to set email alerts
|

Detecting quantitative trait loci for water use efficiency in rice using a recombinant inbred line population

Abstract: Breeding rice with high water use efficiency (WUE) can ameliorate water shortage through water-saving irrigation. However, WUE is a complex quantitative trait and very few studies have been conducted to measure WUE directly. In this study, a recombined inbred line population derived from a cross between an indica lowland rice and upland japonica rice was used to dissect the genetic control of WUE by fine-monitored water supply experiments. Quantitative trait loci (QTL) were scanned for 10 traits including head… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…QTLs identified with small effects also contributed to the genetic control of complex polygenic traits. Small-effect QTLs for complex traits are highly polygenic in nature and have been reported in many crops, including maize [ 50 ] and rice [ 51 ]. Indeed, the contribution of each locus may be negligible, but the total contribution is usually significant for such complex traits.…”
Section: Discussionmentioning
confidence: 99%
“…QTLs identified with small effects also contributed to the genetic control of complex polygenic traits. Small-effect QTLs for complex traits are highly polygenic in nature and have been reported in many crops, including maize [ 50 ] and rice [ 51 ]. Indeed, the contribution of each locus may be negligible, but the total contribution is usually significant for such complex traits.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, QTL mapping has been applied for crop improvement (Kumar and Kumar, 2009), and a large number of molecular markers linked with traits have been obtained; moreover, some QTLs controlling agronomic traits have been successfully cloned (Zhou et al, 2011). In maize, numerous QTLs have been identified that control agronomic traits, and these QTLs have been mapped to 10 chromosomes in maize (Tsonev et al, 2009;Qiu et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In comparison, the recombinant inbred line (RIL) population is immortal and can be used in different regions and times because it consists of homogenous individuals. The RIL population has been widely used for QTL mapping in crops (Balint-Kurti et al, 2008;Du et al, 2009;Blair et al, 2010;Zhou et al, 2011), but it has rarely been used for QTL mapping for traits associated with plant architecture in maize (Tang et al, 2007;Liu et al, 2010). Additionally, the same type of segregating population derived from different parental lines likely provide different QTL identification results, including different location, number, and genetic effects.…”
Section: Introductionmentioning
confidence: 99%
“…The PVE of these M-QTLs were low indicating minor effect QTLs. Small-effect QTLs for complex traits such as yield were also been identified in rice ( Oryza sativa L.) (Zhou et al 2011 ) and maize ( Zea mays L.) (Ribaut et al 1997 ). These results confirm the current understanding that the complex traits are highly polygenic in nature and are the outcome of several small-effect genetic factors.…”
Section: Discussionmentioning
confidence: 99%